Inheritance Law of Children Outside of Marriage - Widya Putri, Meyrara (Jurnal Ilmu Hukum Tambun Bungai, 2023)
Inheritance law has an important role in people's lives, especially in terms of regulating rights to property left by someone who has died. However, in practice, the implementation of inheritance law in Indonesia still faces various challenges, such as differences in views between heirs and the court, ambiguity in the inheritance process, and the determination of heirs which can lead to conflicts and disputes between the families left behind. Therefore, it is necessary to conduct a more in-depth study of inheritance law in Indonesia to improve implementation and provide solutions to problems that arise. This study uses the literature review method of literature on books related to the theme of the papers made, and also sources from dictionaries and several articles from the internet. It was found that there are two legal bases for an expert to inherit a number of the heir's assets according to the BW inheritance legal system, namely according to the provisions of the law and appointed in a will. Inheritance must occur under the condition that the heir must have passed away (Article 830 of the Civil Code) and conditions related to the heir. The person who is entitled or the heir to the inheritance must have existed or was still alive at the death of the heir. A child out of wedlock may only inherit his father's inheritance if this father recognizes him as his son, but he may not inherit class II, class III and class IV inheritance. He may inherit inheritance from all groups if he is recognized as legitimate, namely the recognition that was ratified in the District Court. Even though he has been recognized as legitimate, what he gets in inheriting is not the same as a legitimate child.